Ulat Kantung (Lepidoptera : Acrolophidae) Hama Utama Kelapa Sawit: Kelimpahan Populasi, Tingkat Serangan dan Musuh Alami Pada Perkebunan Rakyat - siska chiko efendi (CROP AGRO, Scientific Journal of Agronomy, 2020)
The abundance of sac caterpillar populations in a oil palm plantation ecosystem is very important to know so that farmers can know the losses that can be caused and overcome the attack of sac caterpillars on oil palm plants and to know the types of natural enemies of sac caterpillars so that the control based on the IPM concept can be applied. This study aims to determine population abundance and sac caterpillars (Lepidoptera: Acrolophidae) pests and natural enemies in smallholder oil palm plantations. Sampling was carried out 3 times at the locations of Nagari Padang Laweh and Nagari Muaro Sopan in March-May 2019 using the survey method and observing sac caterpillars and natural enemies carried out by direct collection. Samples that have been obtained from each observation point are counted by the number of larvae and natural enemies. The results showed that higher rates of sac caterpillar attacks occurred in Nagari Padang Laweh. At the location in Padang Laweh, the total population collected was 793, and at the Muaro Sopan location, 41 caterpillars were found. The highest percentage of sac caterpillar attacks in the Padang Laweh location sample was 76.92%, and the lowest percentage of attacks in the Muaro Sopan location sample was 35.89%. The rate of attack of the sac caterpillar on the 9th midrib is 30.00 tails per midrib which is included in the weight category. Natural enemies found in both study sites are predators of spider types.